The Known Unknowns of Petrogenic Organic Carbon in Soils - Daniel L. Evans; Sebastian Doetterl; Nora Gallarotti; Eleanor Georgiadis; Sami Nabhan; Stephan H. Wartenweiler; Timo M. Y. Rhyner; Benedict V. A. Mittelbach; Timothy I. Eglinton; Jordon D. Hemingway; Thomas M. Blattmann (AGU Advances)
Abstract Intensifying effects of global climate change have spurred efforts to enhance carbon sequestration and the long‐term storage of soil organic carbon (OC). Current soil carbon models predominantly assume that inputs of OC are biospheric, that is, primarily derived from plant decomposition. However, these overlook the contribution of OC from soil parent material, including petrogenic organic carbon (OCpetro) from OC‐bearing (meta‐)sedimentary bedrock. To our knowledge, no soil carbon model accounts for the inputs of OCpetro to soils, resulting in significant gaps in our understanding about the roles OCpetro plays in soils. Here, we call for cross‐disciplinary research to investigate the transport and stability of OCpetro across the bedrock–soil continuum. We pose four key questions as motivation for this effort. Ignoring the inputs of OCpetro to soils has significant implications, including overestimating biospheric carbon stocks and turnover times. Furthermore, we lack information on the role that OCpetro may play in priming microbial communities, as well as the impacts of land management on OCpetro stocks.